Comparison between Unilateral and Bilateral Plyometric Training on Single and Double Leg Jumping Performance and Strength. - Bogdanis, Gregory C; Tsoukos, Athanasios; Kaloheri, Olga; Terzis, Gerasimos; Veligekas, Panagiotis; Brown, Lee E (J Strength Cond Res, 2017)
This study compared the effects of unilateral and bilateral plyometric training on single and double-leg jumping performance, maximal strength and rate of force development (RFD). Fifteen moderately trained subjects were randomly assigned to either a unilateral (U, n=7) or bilateral group (B, n=8). Both groups performed maximal effort plyometric leg exercises two times per week for 6 weeks. The B group performed all exercises with both legs, while the U group performed half the repetitions with each leg, so that total exercise volume was the same. Jumping performance was assessed by countermovement jumps (CMJ) and drop jumps (DJ), while maximal isometric leg press strength and RFD were measured before and after training for each leg separately and both legs together. CMJ improvement with both legs was not significantly different between U (12.1±7.2%) and B (11.0±5.5%) groups. However, the sum of right and left leg CMJ only improved in the U group (19.0±7.1%, p<0.001) and was unchanged in the B group (3.4±8.4%, p=0.80). Maximal isometric leg press force with both legs was increased similarly between groups (B: 20.1±6.5%, U: 19.9±6.2%). However, the sum of right and left leg maximal force increased more in U compared to B group (23.8±9.1% vs. 11.9±6.2%, p=0.009, respectively). Similarly, the sum of right and left leg RFD0-50 and RFD0-100 were improved only in the U group (34-36%, p<0.01). Unilateral plyometric training was more effective at increasing both single and double-leg jumping performance, isometric leg press maximal force and RFD when compared to bilateral training.